Availability of assisted peritoneal dialysis in Europe: call for increased and equal access. Issue 11 (7th June 2022) - Brown, Edwina A; Ekstrand, Agneta; Gallieni, Maurizio; Gorrín, Maite Rivera; Gudmundsdottir, Helga; Guedes, Anabela Malho; Heidempergher, Marco; Kitsche, Benno; Lobbedez, Thierry; Lundström, Ulrika Hahn; McCarthy, Kate; Mellotte, George J; et al.
ABSTRACT: Background: Availability of assisted PD (asPD) increases access to dialysis at home, particularly for the increasing numbers of older and frail people with advanced kidney disease. Although asPD has been widely used in some European countries for many years, it remains unavailable or poorly utilized in others. A group of leading European nephrologists have therefore formed a group to drive increased availability of asPD in Europe and in their own countries. Methods: Members of the group filled in a proforma with the following headings: personal experience, country experience, who are the assistants, funding of asPD, barriers to growth, what is needed to grow and their top three priorities. Results: Only 5 of the 13 countries surveyed provided publicly funded reimbursement for asPD. The use of asPD depends on overall attitudes to PD, with all respondents mentioning the need for nephrology team education and/or patient education and involvement in dialysis modality decision making. Conclusions and call to action: Many people with advanced kidney disease would prefer to have their dialysis at home, yet if the frail patient chooses PD most healthcare systems cannot provide their choice. AsPD should be available in all countries in Europe and in all renal centres. The top priorities to make this happen are education of renal healthcare teams about the advantages of PD, education of and discussion with patients and their families as they approach the need for dialysis, and engagement with policymakers and healthcare providers to develop and support assistance for PD.